Pengkaderan dan Dakwah Sebagai Basis Gerakan (Studi Kasus Ormas Hidayatullah) - Taufik Hidayat; Sulthan Kemal Faza; Aryanti Nur Zaimah; Slamet Mulyono Redjosari (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2022)
The term "Islamic Movement" in the last decade has been confused, because some groups often associate it with radical movements, terrorism, to justify all means to achieve their political goals. This kind of meaning seems to send a negative message to the Islamic movement in Indonesia that has long struggled to build the nation. The term "movement" attached to each Islamic organization actually refers to two important concepts; renewal and reform. This research wants to reveal what kind of role Ormas Hidayatullah fights to build the nation. Starting from the history of its establishment, the concept of wiring and da'wah applied to the profile of its founder. The method used is library study, where the author collects, reads and learns various references relevant to the theme carried out in this journal article. The results showed that Hidayatullah's organization is a religious social organization that makes the empowerment and da'wah as the basis of his movement. The basis of hidayatullah's orams footing as orams da'wah as well as a paradigm da'wah for its cadres, namely, the Qur'an and Sunnah of the Prophet SAW. Currently, Ormas Hidyatullah has branches in various cities in Indonesia, even abroad.